2011
DOI: 10.1155/2011/587457
|View full text |Cite
|
Sign up to set email alerts
|

Liaison Old Age Psychiatry Service in a Medical Setting: Description of the Newcastle Clinical Service

Abstract: Liaison Old Age Psychiatry services (LOAP) have begun to emerge in the UK and further development of the service is supported by the latest health policies. Since qualitative and quantitative studies in this area are lacking, we have undertaken a detailed quantitative prospective review of referrals to the Newcastle LOAP to evaluate the clinical activity of the service. We report high referral rates and turnover for the LOAP service. Reasons for referral are diverse, ranging from requests for level of care and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…Liaison Services for Older Adults (LSOA) are among those that are numbered in the list of small subspecialties. Our analysis of the LSOA within our locality 2 and wider 3 confirms that the LSOAs appear to be the fastest growing liaison discipline. In Newcastle alone we witness a steady 10% yearly increase of older people referred to our service, with the overall numbers being very close to those of our Deliberate Self Harm (DSH) team (37% LSOA v .…”
supporting
confidence: 66%
“…Liaison Services for Older Adults (LSOA) are among those that are numbered in the list of small subspecialties. Our analysis of the LSOA within our locality 2 and wider 3 confirms that the LSOAs appear to be the fastest growing liaison discipline. In Newcastle alone we witness a steady 10% yearly increase of older people referred to our service, with the overall numbers being very close to those of our Deliberate Self Harm (DSH) team (37% LSOA v .…”
supporting
confidence: 66%
“…The conclusion evidenced a lack of ownership and responsibility for these services, and further evaluation of liaison mental health service for older people was highly recommended 43. A recent quantitative prospective review of referrals to a psychiatry liaison service (Newcastle, United Kingdom) showed a significant increase in cognitive assessments (from 19% to 49%) 44. The effect of service on psychological support to patients, cost, staff training, and outcome, including length of stay and readmission, were not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Except for a limited research work completed on service development and characterisation of the Liaison team for older adults [35], there is very little additional academic work in relation to the Liaison professional activity. Our pilot data on current scope of work by seven Liaison services in the UK indicates that education is one of the major gaps in the Liaison services [36] and needs to be urgently addressed in the light of the latest Commissioning and Quality framework for dementia and delirium.…”
Section: The Future Of Liaison Psychiatry Servicesmentioning
confidence: 99%